2015
DOI: 10.1093/hmg/ddv197
|View full text |Cite
|
Sign up to set email alerts
|

Knockout ofRP2decreases GRK1 and rod transducin subunits and leads to photoreceptor degeneration in zebrafish

Abstract: Retinitis pigmentosa (RP) affects about 1.8 million individuals worldwide. X-linked retinitis pigmentosa (XLRP) is one of the most severe forms of RP. Nearly 85% of XLRP cases are caused by mutations in the X-linked retinitis pigmentosa 2 (RP2) and RPGR. RP2 has been considered to be a GTPase activator protein for ARL3 and to play a role in the traffic of ciliary proteins. The mechanism of how RP2 mutations cause RP is still unclear. In this study, we generated an RP2 knockout zebrafish line using transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 51 publications
3
42
0
Order By: Relevance
“…Knockdown of Ift172 results in the loss of photoreceptors as well (Bujakowska et al, 2015). Reverse genetic mutations in the CC/TZ protein CC2D2A (Bachmann-Gagescu et al, 2011), axoneme protein RP2 (Liu et al, 2015), and myosin 7A (Wasfy et al, 2014) result in photoreceptor degeneration in zebrafish, indicating that zebrafish are an excellent model for the study of photoreceptor diseases associated with ciliopathies. In the case of EYS, it is difficult to model RP25 in the mouse due to the lack of an EYS gene.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of Ift172 results in the loss of photoreceptors as well (Bujakowska et al, 2015). Reverse genetic mutations in the CC/TZ protein CC2D2A (Bachmann-Gagescu et al, 2011), axoneme protein RP2 (Liu et al, 2015), and myosin 7A (Wasfy et al, 2014) result in photoreceptor degeneration in zebrafish, indicating that zebrafish are an excellent model for the study of photoreceptor diseases associated with ciliopathies. In the case of EYS, it is difficult to model RP25 in the mouse due to the lack of an EYS gene.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a gene-trap mouse model of Rp2 ablation was reported to have a relatively delayed defect in both cones and rods and associated with defective trafficking of prenylated proteins [Zhang et al, 2015]. Moreover, a zebrafish model of rp2 ablation was recently reported [Liu et al, 2015]. This model develops an early rod and cone dysfunction but a preservation of the morphology of the retina up to 7 months of age.…”
Section: Composition Of Rp2 Mutant Cosmentioning
confidence: 99%
“…Notably, Drosophila possesses a compound eye, however, humans lack this compound eye structure. Because zebrafish has a similar retinal structure and a cone-dominant vision like in humans2223, and is a widely used animal model in biological research242526, it confers advantages to better interpret the pathological and molecular mechanisms of EYS mutations. Very recently, an independent study with EYS -knockout zebrafish was reported by Yu et al 27…”
mentioning
confidence: 99%